Viking Vik and the secret Shield. Viking Vik - Rayner, Shoo (London: Orchard, 2009)
"Viking Vik's grandmother tells him a story that leads him into a real adventure. Is Vik brave enough to enter the Underground Kingdom and claim the prize that waits for him in the darkness?"--Publisher description
Keywords: Adventure stories